2007
DOI: 10.1139/v07-056
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the influence of fission product doping on the anodic reactivity of uranium dioxide

Abstract: The influence of fission product doping on the structure, composition, and electrochemical reactivity of uranium dioxide has been studied using X-ray diffractometry (XRD), scanning electron microscopy (SEM/EDX), Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS). Experiments were conducted on SIMFUEL specimens with simulated burn-ups (increasing doping levels) of 1.5, 3.0, and 6.0 atom%. As the dopant level increased, the lattice contracted, suggesting the dominant formation of dopant-oxygen vacanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 42 publications
8
30
0
Order By: Relevance
“…The current results thus support the suggestion from Ref. [14] that the effect of increased burnup (leading to higher concentrations of soluble trivalent fission products) on oxidative corrosion rates in spent nuclear fuel can be attributed to lower oxygen mobility due to defect association.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current results thus support the suggestion from Ref. [14] that the effect of increased burnup (leading to higher concentrations of soluble trivalent fission products) on oxidative corrosion rates in spent nuclear fuel can be attributed to lower oxygen mobility due to defect association.…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, recent studies have attributed rare earth (i.e. trivalent) fission product dopant-oxygen vacancy clusters to the decreased rate of oxidative dissolution with increasing burnup in spent fuel [14]. The defect clusters are believed to reduce the concentration of mobile oxygen vacancies which facilitate oxidation and eventual dissolution of the fuel, in a manner similar to that by which rare earth doping impedes air oxidation of the cubic fluorite structure to orthorhombic U 3 O 8 [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…X-ray photoelectron spectroscopic data on SIMFUEL suggest an increase in U(V) at the expense of U(IV) with increasing trivalent doping [21]. Furthermore, at doping levels up to 3 at.%, the electrical conductivity increases with increasing rare earth content.…”
Section: Introductionmentioning
confidence: 95%
“…Spent nuclear fuel [16][17][18][19], SIMFUEL [20,21], UO 2 pellets with palladium (as a model substance for metallic e-phase particles) [2,3], a-doped [4,19] and pure UO 2 [2,3,22] have been studied in dissolution and electrochemical experiments. From experiments under H 2 atmosphere, it has been shown that spent nuclear fuel, a-and Pd-doped UO 2 show lower U(VI) dissolution [2][3][4]19,23,24], and that the corrosion potential of SIMFUEL is significantly reduced [20].…”
Section: Introductionmentioning
confidence: 99%
“…for U(IV) contributes to increased electrical conductivity [25]. However, recent results, presented by He et al [26], indicate that the structural changes occurring from the incorporation of fission products decrease the UO 2 dissolution rate. Noble metal fission products present in the spent nuclear fuel are known to congregate to nanometersized particles (e-particles) [27].…”
Section: Factors Influencing the Solid Phase Reactivitymentioning
confidence: 97%